Health Systems Research in a Complex and Rapidly Changing Context: Ethical Implications of Major Health Systems Change at Scale. Issue 3 (9th March 2016) - MacGregor, Hayley; Bloom, Gerald
Abstract: This paper discusses health policy and systems research in complex and rapidly changing contexts. It focuses on ethical issues at stake for researchers working with government policy makers to provide evidence to inform major health systems change at scale, particularly when the dynamic nature of the context and ongoing challenges to the health system can result in unpredictable outcomes. We focus on situations where 'country ownership' of HSR is relatively well established and where there is significant involvement of local researchers and close ties and relationships with policy makers are often present. We frame our discussion around two country case studies with which we are familiar, namely China and South Africa and discuss the implications for conducting 'embedded' research. We suggest that reflexivity is an important concept for health system researchers who need to think carefully about positionality and their normative stance and to use such reflection to ensure that they can negotiate to retain autonomy, whilst also contributing evidence for health system change. A research process informed by the notion of reflexive practice and iterative learning will require a longitudinal review at key points in the research timeline. Such review should include the convening of a deliberative process and should involve a range of stakeholders, including those most likely to be affected by the intended and unintended consequences of change.